A preferred patient decubitus positioning for magnetic resonance image guided online adaptive radiation therapy of pancreatic cancer. (October 2019) - Chen, Yazheng; Chen, Xinfeng; Hall, William; Prior, Phil; Zhang, Ying; Paulson, Eric; Lang, Jinyi; Erickson, Beth; Li, X. Allen
Highlights: Left decubitus positioning increases separation between duodenum and pancreas. The increase improves duodenum sparing during radiotherapy of pancreatic cancer. Daily MRI-guided adaptation facilitates the left decubitus positioning. Abstract: Background and purpose: In radiotherapy (RT) for pancreatic cancer, the dose to adjacent organs-at-risk (OAR) often limits the delivery of curative dose. This work aimed to find a body decubitus position that would lead to increased separation between the duodenum and pancreatic head. Materials and methods: Abdominal magnetic resonance images (MRI) of 11 healthy volunteers were acquired using a 1.5T MR-Linac for supine, left decubitus and right decubitus body positions. The geometry changes between different body positions were measured using Hausdorff Distance (HD) and overlap volume. RT plans were created on the MRIs. Commonly used dose-volume parameters (DVP), e.g., V40Gy – volume received at least 40 Gy, for OARs were compared for the three body positions. Results: The average of maximum HD between the duodenum and pancreatic head for all the cases was 4.0 ± 3.1 mm for supine, 7.3 ± 4.4 mm for left and 3.3 ± 1.4 mm for right positions (P < 0.01). The DVPs of the duodenum (e.g., V20Gy, V45Gy ) for the left position were lower than those for the supine and right positions ( P  < 0.01). The right decubitus led to the highest duodenum DVPs. On average, the highest dose escalation was increased from 69 ± 4 Gy to 74 ± 5 Gy ( P  = 0.002) if body position was changed from supine to left decubitus. Conclusion: The left decubitus increased the separation between duodenum and pancreas head, improving OAR sparing in RT for pancreatic cancer and allowing safer dose escalations to the tumor. The left decubitus positioning with proper immobilization could be adopted for MRI-guided adaptive RT.